Domestic gardens and morbidity: Associations between private green space and diagnosed health conditions in the Netherlands - Sjerp de Vries; Christos Baliatsas; Robert Verheij; Michel Dückers (Environment International)
Background: Previous studies observed predominantly positive associations between the amount of nearby green space and a variety of health outcomes. Although nearness is assumed to be an important aspect of this association, the presence of own private green space is rarely studied. We investigated cross-sectional associations between the amount of domestic garden greenery and the prevalence of 21 health conditions. Methods: Electronic health records of general practitioners, providing data on health conditions of individuals and where they lived for the year 2018, were linked with data from the same year on garden presence and size derived from the Netherlands’ Cadastre, Land registry and Mapping Agency. Amount of garden greenery was assessed with high resolution aerial photographs. Data were available for about 800,000 persons from 294 practices. We performed multi-level logistic regression analyses with practice as second level, adjusting for multiple covariates, including socioeconomic status at individual and neighbourhood level. Findings: Prevalence of 16 of the 21 health conditions was lower for at least the highest classes of garden greenery. The inverse association was strongest for intestinal tract infections, with an over 20 % lower prevalence if the garden contained at least 50 m2 greenery versus no garden. Including the overall amount of greenery within 125 m of the home in the analyses did not attenuate the results. Sex was an important moderator, with many associations being stronger for women. Conclusions: Own private green space is inversely associated with the prevalence of many health conditions, more so than other nearby green space. Responsible pathways are unclear. Further research is needed to confirm these findings and to identify the pathways underlying the cross-sectional associations. Information on pathways may also offer clues on how to compensate for the absence of a domestic garden, which is likely to become more common due to urban densification.